Analisis Kapasitas Settling Pond Berdasarkan Pengaruh Laju Sedimentasi Area Cluster Volvo PT Kaltim Prima Coal - Maxxy Charlie Fadda Malikus Putra; Peter Eka Rosadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Open-pit mining activities at PT Kaltim Prima Coal have altered land use, thereby increasing erosion and sedimentation potential. The Cluster Volvo area is characterized by surface runoff that transports sedimentary material into settling ponds. This study aims to analyze the capacity of the settling ponds in the Cluster Volvo area based on the planned flood discharge using the HSS Nakayasu method, as well as total erosion and sedimentation calculated via the USLE method, to establish a maintenance schedule for the ponds. The results indicate that the Volvo Pond requires a capacity upgrade. Based on the calculated flood discharge and total erosion, the crest elevation of the Volvo Pond needs to be adjusted from RL+35.5 to RL+36.5. Consequently, this settling pond capacity analysis serves as a technical recommendation for the company to address issues related to water retention and sedimentation that lead to pond overtopping.